The Role of the Family in Character Education for Early Age Children 0-8 Years - Difly Praise Malelak; Marisa Aulia Gea (Elementaria: Journal of Educational Research, 2023)
The family is the first place of education for a child in his life, which is the basis for forming a child's character and education. This research aims to explore the role of the family in educating children's character. The research method used is a qualitative method where the author seeks various information regarding the role of the family in educating the character of early childhood from various information regarding this matter. And here the role of the family is very important in educating a child to have good character, without a good family the child will not experience good character growth and development.